Hydrocolloids in food processing - Laaman, Thomas (IFT Press series., 2011)
"In Hydrocolloids in Food Processing, a group of the most experienced and impartial experts explains what stabilizers should be used and how they should be used, food product by food product. Numerous actual product formulations are packed into each chapter and the processing procedures to make these formulations are clearly described. Food manufacturers are shown how to accurately use food stabilizers to make the highest quality food products. Coverage includes all the practical details needed to ensure the most accurate QA standards and testing procedures for each hydrocolloid. Finally, Hydrocolloids in Food Processing explains how to navigate the often tricky area of dealing with hydrocolloid suppliers. An informative discussion of how hydrocolloid companies think and operate today is followed by precise strategies to ensure that the most mutually beneficial relationships can be obtained between specific customer types and appropriate types of suppliers"--Provided by publisher